2020
DOI: 10.1186/s12954-020-00447-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of skin and soft tissue infections among sample of rural residents who inject drugs

Abstract: Introduction Skin and soft tissue infections (SSTIs) are among the leading causes of morbidity and mortality for people who inject drugs (PWID). Studies demonstrate that certain injection practices correlate with SSTI incidence among PWID. The opioid epidemic in the USA has particularly affected rural communities, where access to prevention and treatment presents unique challenges. This study aims to estimate unsafe injection practices among rural-dwelling PWID; assess treatments utilized for i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
(61 reference statements)
0
10
1
Order By: Relevance
“…The prevalence of injection drug use in the United States has been estimated to be 0.24% to 0.59% of the noninstitutionalized population of the United States, which is an estimated 1 million people 11 . There are no current published statistics on the incidence of SP in the general population, likely due to the stigma of illicit drug use, the continued use of open wounds as “shooter's patches,” and the self-treatment of infections outside of the hospital setting using antibiotics and drainage 12,13 . Patients typically present to medical care because of the sequelae of SP, such as cellulitis, wound botulism, renal dysfunction, or large wounds.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The prevalence of injection drug use in the United States has been estimated to be 0.24% to 0.59% of the noninstitutionalized population of the United States, which is an estimated 1 million people 11 . There are no current published statistics on the incidence of SP in the general population, likely due to the stigma of illicit drug use, the continued use of open wounds as “shooter's patches,” and the self-treatment of infections outside of the hospital setting using antibiotics and drainage 12,13 . Patients typically present to medical care because of the sequelae of SP, such as cellulitis, wound botulism, renal dysfunction, or large wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings are mostly consistent with our study, which found that patients typically used injection sites on the dorsal hands and forearm followed by the upper arm without mention of using the antecubital fossa. There has not been a demonstrated correlation between the rate of infection and the location of injection within the upper extremity 13 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations